Risk Factors for Post-Cesarean, Surgical Site Infections in a Multi-Ethnic Population of Qatar - Sufia Athar (14777830) (2024)
Background The surgical site infection (SSI) rate after Cesarean delivery (CD) is considered one of the key performance indicators, not only for developing and under-developed countries but also for developed nations. SSIs not only increase patients’ morbidity and mortality rates, but also lay a huge economic burden. In our hospital, the SSIs after CD were noted to increase in 2016 and first quarter of 2017. One of the methods implemented for SSI reduction included identifying modifiable risk factors. Methods A case-control study was conducted at a secondary hospital in Qatar after institutional approval. Retrospective analysis of risk factors and microbiological spectrum was carried out in women who delivered by Cesarean Section between 2017-2020. Women who did not develop SSIs were taken as control group and selected with a blind sampling technique. The risk assessment was compared with a control population. The Odds’ ratio was calculated for statistical analysis of results. A look into the causative organism was performed to assess if the antibiotic prophylaxis was appropriate. Results 8,372 women delivered by Cesarean section during the study timeframe. Out of these 1.51% developed SSIs. Nearly two-thirds had superficial wound infections. 87% of these cases were diagnosed between 8-28 days of CD. Gestational diabetes, anemia, body mass index >30kg/m2, prolonged rupture of membranes >24 hours, and chorioamnionitis were identified as risk factors (p<0.05) (Figure 1). The most common organisms for SSIs were Staphylococcus aureus (25.58%), E. coli (27.13%) and Klebsiella pneumonia (10.08%). Multiple drug-resistant organisms were isolated in 17.83% of cases. Conclusion This study provides baseline levels for SSI after CD across several different patient subgroups. SSIs with multiple drug-resistant organisms were significantly high. Physicians should give special attention to modifiable risk factors and antibiotic stewardship to decrease the risk of SSI and improve patient outcomes.